Consórcios com plantas de cobertura em segunda safra na região de ecótono do Cerrado-Amazônia - Alves Filho, Renato Candido (2023)
The Cerrado-Amazon ecotone region, characterized by high temperature and humidity, distinct from the conditions commonly found in the Cerrado, is undergoing agricultural expansion. Few studies are presented to help choose the best species of cover crops in local production systems. This study has the following questions: (i) Which are the best cover species that promote soil conditions and soybean productivity in integrated systems? (ii) Are soil biological indicators good parameters to monitor soil conditions in integrated systems? To answer these questions, the objective of the study was to monitor the availability of nutrients and the enzymatic activity of the soil with intercropping of forage plants in the second harvest, after the soybean harvest. In addition, we seek to understand the use of soil biological indicators in monitoring soil conditions in integrated systems. The study was carried out at the Experimental Station of Embrapa Agrossilvipastoril, located in Sinop, Mato Grosso, Brazil, between 2016 and 2022, in a production area with seven consortiums using the forages: Urochloa brizantha, Urochloa ruziziensis, Cajanus cajan, Vigna unguiculata, Helianthus annuus, Crotalaria ochroleuca, Crotalaria spectabilis, Raphanus sativus L., Guizotia abyssinica and Fagopyrum esculentum. Results showed that the coverings with brachiaria (Urochloa ruziziensis) + Crotalaria spectabilis or brachiaria (Urochloa ruziziensis) + radish (Raphanus sativus L.) showed the highest availability of nutrients, organic matter and activities of arylsulfatase and beta-glucosidase in the soil. The physical, chemical and biological indicators of the soil were efficient in measuring changes in the soil. Based on the results, it concludes that cover crops contribute to improving soil quality, especially when associated brachiaria with forage radish or crotalaria.